2020
DOI: 10.1093/nutrit/nuaa019
|View full text |Cite
|
Sign up to set email alerts
|

Associations of maternal stress and/or depressive symptoms with diet quality during pregnancy: a narrative review

Abstract: Background Pregnancy can be a stressful time for many women; however, it is unclear if higher stress and depressive symptoms are associated with poorer diet quality during pregnancy. Objective The aims for this narrative review were to (1) synthesize findings of original, peer-reviewed studies that examined associations of stress and/or depressive symptoms with diet quality during pregnancy; (2) review the measurement tools u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 80 publications
1
12
3
Order By: Relevance
“…We also found that reporting moderate to severe depressive symptoms during pregnancy was associated with lower dietary quality. Our findings for depressive symptoms are consistent with previous, though limited, literature suggesting that maternal mental health, including depression and anxiety, is associated with unhealthy dietary intakes (using various dietary assessments) (52,53). This is of concern because both poor maternal mental health and poor dietary intakes increase the risk of adverse birth outcomes, such as preterm birth and low birth weight (54,55), and later childhood health outcomes (56,57).…”
Section: Discussionsupporting
confidence: 88%
“…We also found that reporting moderate to severe depressive symptoms during pregnancy was associated with lower dietary quality. Our findings for depressive symptoms are consistent with previous, though limited, literature suggesting that maternal mental health, including depression and anxiety, is associated with unhealthy dietary intakes (using various dietary assessments) (52,53). This is of concern because both poor maternal mental health and poor dietary intakes increase the risk of adverse birth outcomes, such as preterm birth and low birth weight (54,55), and later childhood health outcomes (56,57).…”
Section: Discussionsupporting
confidence: 88%
“…To maintain a healthy pregnancy, adequate nutrition is needed to nourish both mother and fetus. A narrative review by Boutté et al (2021) confirmed that worldwide, women with depression or stress during pregnancy eat an unhealthy diet, high on fat, and low in fruits and vegetables. Aspects of the prenatal diet related to fat consumption have been associated with changes to pregnancy and infant gut microbiota (Chu et al, 2016;Mandal et al, 2016).…”
Section: Prenatal Depression Influences the Infant's Gut Microbiome Independent Of Prenatal Dietmentioning
confidence: 94%
“…Maternal stress may also be linked to child obesity [37][38][39], but the mechanisms explaining this link are largely unknown. We propose two main pathways that may explain this link during lactation (see Figure 1), that is, one physiological pathway (i.e., through human milk composition) [40,41] and one behavioral one (i.e., through maternal lifestyle and weightrelated parenting) [42,43] affecting child weight-related behaviors [44]. Future research may examine whether and how intervention on maternal stress may impact human milk components and child weight outcomes through lactation-specific pathways (i.e., child satiety and eating characteristics, child gut microbiota, and flavor exposure).…”
Section: Future Intervention Research Agendamentioning
confidence: 99%